2020
DOI: 10.1111/jth.14707
|View full text |Cite
|
Sign up to set email alerts
|

May‐Thurner syndrome: History of understanding and need for defining population prevalence

Abstract: Patients with May‐Thurner syndrome (MTS) are at elevated risk of developing an extensive left iliofemoral deep vein thrombosis (DVT; localized blood clot) due to an anatomical variant where the right common iliac artery compresses the left common iliac vein against the lumbar spine. While MTS was initially presumed to be rare when it was first anatomically defined in 1957, case reports of this syndrome have recently become more frequent, perhaps due to improved imaging techniques allowing for enhanced visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
100
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 98 publications
(217 reference statements)
1
100
0
2
Order By: Relevance
“…It is estimated to be present in 2% to 5% of patients with lower limb venous disease. [27][28][29] May and Thurner found spur-like projections in the left common iliac vein in 22% of 430 cadavers examined. 2 MTS is underdiagnosed, possibly due to its diagnostic difficulty and permissive role in chronic venous disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is estimated to be present in 2% to 5% of patients with lower limb venous disease. [27][28][29] May and Thurner found spur-like projections in the left common iliac vein in 22% of 430 cadavers examined. 2 MTS is underdiagnosed, possibly due to its diagnostic difficulty and permissive role in chronic venous disease.…”
Section: Discussionmentioning
confidence: 98%
“…2 MTS is underdiagnosed, possibly due to its diagnostic difficulty and permissive role in chronic venous disease. 28 MTS is often asymptomatic, until an additional insult or pathology is superimposed, such as cellulitis or osteoarthritis of the knee resulting in loss of the venous calf pump mechanism. 25,30 A small prospective study on 20 asymptomatic volunteers who underwent angiography of the iliac veins found that 80% had at least 2 signs indicative of MTS.…”
Section: Discussionmentioning
confidence: 99%
“…The true prevalence is still unknown. It ranges from 2-5% as per a few studies [5,6] Autopsy studies suggest a prevalence between 14-32% [5], radiology studies looking at the left lower extremity DVT alone suggest a prevalence from 22% to 76% [5]. A recent case series and extensive discussion by Katalin Mako et al [7] shows how it is often underestimated and needs a high index of suspicion for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 The casecontrol study by Narayan et al found that female sex had odds ratio 6.41 for compression of the left iliac vein, providing an underlying cause for the observed laterality associated with female sex. 7 It has been proposed that the accentuated lordosis of the lower spine in females pushes the left iliac vein forward against the right iliac artery (briefly reviewed by Harbin et al) 24 We did not perform adjustment for multiple comparisons because all analyses were driven by specific hypotheses. 25 Future studies may address whether the left-side predominance is restricted to female sex and what is the extent of its clinical significance.…”
Section: Discussionmentioning
confidence: 99%